PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 003 BELIMBING KECAMATAN BATANG GANSAL KABUPATEN INGRAGIRI HULU - Nadra Nadra; Mahmud Alpusari; Damanhuri Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract. Based on preliminary observations in SDN 003 Belimbing Kecamatan Batang Gansal Kabupaten Indragiri Hulu Found the problems in learning class IV. Teacher deliver the subjed matter only uses one method, The teacher is not able to create on atmospher thet allows students to learn creatively, in the learning process does not involve students and teacher only centered on the teacher allone, students are not active in learning, many students play in learning, students fear asked, the student were not involved. So the impact on students learning outcomes are sttil relatively low and does not meet the standar KKM 65. This type of research is classroom action research with two cycles, each cyles there are four meetings.The subjed this study is fouth grade students of SDN 003 Belimbing Kecamatan Batang Gansal Kabupaten Indragiri Hulu, consisting of 30 students, 10 male students and 20 female students.The data collection technigues from this study is the observation achievement test, and documentation.The results showed the activity of teacher in the first cycle to abtain a score of 11 in the first meeting with less category and a score of 13 in the second meeting with enough category in the second cycle scored 16 in the first meeting with well category and a score of 23 in the second meeting with a good category. Students activity on first cycle abtain a score of 11 category 1 less at a score of 13 meeting, and a score of 13category is guite at the meeting 2 in the second cycle increased by a score of 16 categories either at a meeting of 23 category 1 and score very well on the second meeting.Mastery learning classical first cycle 15,70% and the second cycle inreased to 100%.The conclusion of this study is through the implementation of cooperatif learning model type STAD can increase the activity of the teacher, student activities, and student learning outcomes SDN 003 Belimbing fourth grade in science subjects.Key words: Cooperative Learning Model STAD, Learning outcomes.